Relasi Pendidikan (Agama) dan Kebudayaan - Muzakki, Hawwin (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2019)
: Indonesia is a Republican State, not a theocracy state based on a particular religious teaching. Because that's the importance of compiling an educational formulation based on religious values ​​in general (not from a particular religion). That ideal was initiated by Ki Hadjar Dewantara. Through the reading of philosophical hermeneutics, the author wants to revitalize the educational thinking of Ki Hadjar Dewantara. Formulation of the problem in this study to investigate 1. How was the transformation of culture initiated by Ki Hadjar Dewantara? 2. What is the Education perspective of Ki Hadjar Dewantara? 3. What is the relation between education (religion) and the perspective culture of Ki Hajar Dewantara's thinking? The results of the study revealed that 1. Through the three-way journey: continuous, convergent, concentric, Ki Hadjar tried to compile his argument about maintaining local traditions and embracing them in national culture. 2. Human nature is an independent and outward soul. Practically, the concept of education that he applied in Taman Siswa is by rejecting the teachings of coercion, orders and punishments, because they are deemed inhuman and in accordance with human nature. Whereas, the nature of nationalism is to live together, one country and one nation, with the spirit of nationalism. 3. The relation between education (religion) and culture are each placed in public space (education and culture) and private (religion)